Computational prediction of tertiary structure of the human proteins Hsp27, αB-crystalline and HspB8. - Sáenz-Suárez, Homero; Unidad de Biología Celular y Microscopía. Decanato de Ciencias de la Salud. Universidad Centroccidental Lisandro Alvarado. Barquisimeto (Pontificia Universidad Javeriana, 2011)
Objective: To make computational predictions of the structure of the human proteins Hsp27, αB-crystalline and HspB8. Materials and methods. The prediction of the secondary structure was obtained by a consensus of the programs for secondary prediction GOR 4, nnPred, Sspro, APSSP2, JPredict, Porter, Prof, SOPMA, HNN and Psi-Pred. The models of tertiary structure were built from fragments homologous to proteins with tertiary known structure that were obtained by multiple alignments. Using the primary sequence we obtained the antigenicity profiles of native proteins and we analyzed the profiles of hydrophobicity, polarity, flexibility and accessibility of both native and mutant proteins. Results. Predictions of the secondary and tertiary structures of the studied proteins show that in the three cases, more than 65% are coil regions, 20-25 % are folded sheet and less than 10% are alpha helix. Analyses of the primary structure show that at least one of the studied profiles in every mutation is altered. Conclusions. The comparative analyses of structure suggest that mutations affect the solubility of the mutated proteins and hence affect their function as molecular chaperones Key words: Hsp27, αB-cristalline, HspB8, prediction of secondary structure, computational model of tertiary structure